ANALYSIS OF THE ROLE OF MOTHERS IN FOSTERING GREEN BEHAVIOR IN EARLY CHILDHOOD - Faridy, Faizatul; Mahyana, Mahyana; Munawwarah, Munawwarah; Amelia, Lina; Rohendi, Aulia (Bunayya, 2024)
Environmental issues are one of the global issues that have not been resolved since the 21st century despite many efforts made both through organizational movements and socialization. One of the main causes of environmental problems is waste produced by humans as a result of daily life behavior. This study aims to analyze how the role of mothers in fostering environmental/green behavior attitudes in early childhood and analyze what are the obstacles in implementing green behavior in early childhood at home. The research method used in this study is a qualitative method with a case study research design. The sampling technique used is purposive sampling because the sample to be studied is selected based on certain criteria, namely families who have early childhood with an age range of 4-8 years. The data collection techniques used in this study were observation, interview and documentation techniques. The results of the study found that mothers play an important role in fostering green behavior in early childhood at home. There are several roles of mothers in fostering green behavior at home including as role models, as caregivers or first educators, and as the main managers in managing full households. The obstacles that mothers often face are limited knowledge about green behavior, limited time and resources, environmental influences and family consumption patterns. It is hoped that future research can explore the development of interesting and age-appropriate educational materials that can help educate them about environmental issues in a fun and understandable way.